The Influence of Adverse Childhood Experiences in Pain Management: Mechanisms, Processes, and Trauma-Informed Care - Tidmarsh, Lydia V.; Harrison, Richard; Ravindran, Deepak; Matthews, Samantha L.; Finlay, Katherine A. (Frontiers in Pain Research, 2022)
Adverse childhood experiences (ACEs) have long been identified as a source of persistent vulnerability for physical and psychological health. Thus, the influence of ACEs needs to be prioritised in the context of chronic pain. Culturally, understanding of traumatic experiences is increasing, however, the empirical exploration of ACEs and clinical outcomes remains under-represented and under-explored. Therefore, the present review aims to highlight the role of ACEs in the experience of chronic pain and the impact that such ACEs may have on pain management services and clinical decision making. The objectives are four-fold: (1) to provide an overview of the relationship between ACEs and chronic pain; (2) to identify biopsychosocial mechanisms through which ACEs may increase risk of persistent pain; (3) to highlight the impact of ACEs on patient adherence and completion of pain management treatment; and (4) in light of this evidence, to provide practical clinical implications for pain management. In chronic pain, ACEs are associated with greater pain complications, pain catastrophizing and depression. Not only do ACEs alone predict non-completion of treatment, combining these factors together further increases the risk of early attrition. The pervasive detrimental impacts of the COVID-19 pandemic on ACEs and its cyclical effects on pain are also discussed in the context of psychological decline during long waitlists. The review highlights how clinically, patients can be supported through a trauma-informed workforce, employing ACEs awareness approaches which acknowledge the patient experience to improve pain and health outcomes. Clinicians who are ACE-informed aims to minimise the negative influence of ACEs on treatment outcomes, ultimately optimising the impact of pain management services.